Like or Not Like Studying Science: Exploring Students’ Personal and Cultural Characteristics - Nasser Mansour (17541822) (2025)
This research examines students’ interests in studying science in the UK, focusing on the context of declining interest in science subjects. A total of 1618 students aged 10 to 14 participated, responding to a questionnaire covering various constructs, such as subject preferences, stereotypes of science people, science extracurricular activities, career pathways, and views of science. Descriptive and inferential analyses, including three models of multiple regression, revealed several key findings. Students from non-Western backgrounds showed lower engagement in science extracurricular activities compared to their Western counterparts. Engagement in science-related activities positively influenced students’ views of science. Interestingly, students’ educational background (primary or secondary education) had a negative impact on their views of science. The study also highlighted a preference for non-STEM subjects over specific STEM fields, with curiosity and hands-on learning influencing favourite subjects. Addressing stereotypes and promoting gender equity in science education are essential. Early educational experiences and science extracurricular activities positively impacted students’ liking for science. Students’ views of science were influenced by hands-on experiences, gender, and educational background, indicating the need to challenge stereotypes. These insights inform science education policy and practice to promote interest and engagement among young learners in the UK. Other Information Published in: Canadian Journal of Science, Mathematics and Technology Education License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s42330-025-00352-6